THE ROLE OF THE CIRCULAR ECONOMY: STRATEGIES TOWARDS GREEN ECONOMIC GROWTH - Muthmainnah; Ardelia Suharmanto; Maulidia Berlianti (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
A circular economy is an approach to an economic system that focuses on the efficient use of resources, reducing waste, and returning materials to the production cycle. This concept aims to overcome limited natural resources, reduce environmental impacts, and create long-term sustainability in economic activities. In a circular economy, resources are considered valuable and kept within the economic circle for as long as possible. This approach differs from traditional linear economic models that focus on resource extraction, production, use, and disposal as waste. Green economic growth is seen as a solution to the exploitative economic system which has tended to damage the environment. The green economy and circular economy have the same goal, namely encouraging economic growth while meeting social and environmental goals. However, both have different focuses. The green economy focuses on encouraging economic growth while taking into account the availability of existing natural resources and ecological balance to ensure sustainability. Meanwhile, the circular economy focuses more on optimizing the use of resources, such as recovering and regenerating products and materials. This article employs a form of literature review that includes hypotheses pertaining to the issue under investigation. A methodical and iterative methodology was used to obtain a full grasp of the role of the circular economy: a strategy towards green economic growth—during the literature search for this extensive review. The definition and guiding principles of the circular economy, growth strategies for the green economy, and the interplay between the two are covered in this study.